THE EFFECT OF POLYPROPYLENE FIBERS ON COMPRESSIVE AND SPLIT TENSILE STRENGTH OF LIGHTWEIGHT CONCRETE - Sultan, Mufti Amir; Gaus, Abdul; Yudasaputra, Muhammad Taufiq; Lambado, Zulham; Hi Bayan, Ilman Nofiyanto (International Journal of Research -GRANTHAALAYAH, 2024)
This study was carried out to design lightweight concrete, which is enriched with polypropylene fibers using coarse pumice and sand fine aggregates. Lightweight concrete specimens were classified into distinct groups based on fibers content employed, namely a control group with 0 kg/m³ and the experimental incorporating 0.1 kg/m³, 0.3 kg/m³, 0.5 kg/m³, and 0.7 kg/m³ varying quantities of polypropylene fibers. Subsequently, after a curing period of 28 days, the hardened concrete test was conducted on cylinder specimens measuring 150 mm x 300 mm. The consistency of the fresh concrete mixture was tested using the Abrams cone test, which revealed a decrease in the workability of fibers-reinforced concrete with an increase in fibers volume in the mixture. The test aimed to determine the effect of polypropylene fibers on compressive and tensile strength of lightweight concrete. The optimal compressive and split tensile strength was observed at fibers volume fraction of 0.5, to obtain 7.84 MPa, or 56.68% increase in compressive strength, and 2.12 MPa or 42.86% rise in tensile strength. Based on compressive and split tensile strength obtained from this study, concrete was classified as highly lightweight structural concrete, which served as an insulator.